Early detection, segmentation and quantification of coronary artery blockage using efficient image processing technique - Shakir, Mohsinul Bari; Hossain, Mohammad Amzad; Shams, Khan Mohammad Aymaan; Akib, Faisal Raihan (BRAC University, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.